Dignified death in the Costa Rican Rule of Law: Assisted suicide, a liberal version. - Quesada Jiménez, Jorge (2020)
Assisted suicide is as rare as it is controversial. The author puts it forward from the Costa Rican criminal sphere, with a liberal version, in such a way that its inclusion in the legal system is considered, not only relieving those who provide collaboration, but promoting open conversation and specialized training that allow it to be approached with the rigor that the legal rights involved require.